2014
DOI: 10.1111/mec.12782
|View full text |Cite
|
Sign up to set email alerts
|

Seascape continuity plays an important role in determining patterns of spatial genetic structure in a coral reef fish

Abstract: Detecting patterns of spatial genetic structure (SGS) can help identify intrinsic and extrinsic barriers to gene flow within metapopulations. For marine organisms such as coral reef fishes, identifying these barriers is critical to predicting evolutionary dynamics and demarcating evolutionarily significant units for conservation. In this study, we adopted an alternative hypothesis-testing framework to identify the patterns and predictors of SGS in the Caribbean reef fish Elacatinus lori. First, genetic structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…4B). This prediction is qualitatively consistent with previous estimates of spatial genetic structure for E. lori in Belize (35). This consistency suggests that the logistic model predicts both short-term patterns of dispersal and long-term patterns of gene flow.…”
Section: Resultssupporting
confidence: 81%
“…4B). This prediction is qualitatively consistent with previous estimates of spatial genetic structure for E. lori in Belize (35). This consistency suggests that the logistic model predicts both short-term patterns of dispersal and long-term patterns of gene flow.…”
Section: Resultssupporting
confidence: 81%
“…Additionally, high levels of larval dispersal among populations may diminish signals of IBD at smaller spatial scales over time (D'Aloia et al., 2014). The lack of barriers to larval dispersal may explain why geographic distance did not correlate with the amount of genetic differentiation at the island‐group scale.…”
Section: Discussionmentioning
confidence: 99%
“…However, the identification of genetic structuring within marine species is notoriously difficult due to the lack of clearly identifiable barriers to gene flow and dispersal commonly found within terrestrial systems. Early genetic studies on marine systems worked under the assumption that populations existed in a state of panmixia in the absence of extrinsic barriers, such as ocean currents and continental barriers (Avise, 2000; Taylor & Hellberg, 2006; D'Aloia, Bogdanowicz, Harrison, & Buston, 2014). However, studies have demonstrated clearly that other factors, such as habitat fragmentation and limited dispersal capabilities, may also act as reproductive barriers that restrict gene flow and result in subsequent isolation (Johnson & Black, 1991; Shulman & Bermingham, 1995; Fauvelot, Bernardi, & Planes, 2003; Gonzalez, Knutsen, & Jorde, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Larval dispersal is then expected to influence seascape genetic variations, and the resulting genetic patterns often differ from the classical theory of isolation by distance (Selkoe et al., 2016). Hence, a comprehensive assessment of the drivers of spatial genetic variation in marine populations needs to include in a same framework environmental heterogeneity, geographic isolation, and larval dispersal (D'Aloia, Bogdanowicz, Harrison, & Buston, 2014; Selkoe et al., 2016). To this aim, large‐scale datasets and novel analytical methods are required (Manel & Holderegger, 2013).…”
Section: Introductionmentioning
confidence: 99%